Farid Esack's Hermeneutics in the Study of Women's Freedom and Justice - Ichwayudi, Budi; Azzahro, Sofi; Syabrowi, Syabrowi; Ali, Maulana Ahmad (STAI Serdang Lubuk Pakam, 2024)
Problems in interpreting the concept of the Qur'an have become a significant issue in the discourse of Islamic thought in the modern era. One of the figures who paid great attention to efforts to explore the meaning of the Qur'an is Farid Esack, who used hermeneutic studies as a tool of interpretation. In line with that, this study aims to analyze the study of liberation and justice for women using Farid Esack's hermeneutic thinking. This research uses a qualitative research method with Farid Esack's hermeneutic approach. The results show that the hermeneutics initiated by Farid Esack, namely liberation hermeneutics, uses critical reasoning that places revelation, reality, and interpretation in an interacting relationship. This approach aims to produce interpretations that are oriented towards liberation and justice. The application of Farid Esack's hermeneutics can be seen in his interpretation of women's liberation from oppression and injustice, especially in the context of divorce. One example is the introduction of the concept of iddah as mentioned in the Qur'an surah Al-Baqarah verse 228 and the relevant hadith. Esack explains that a wife is still entitled to receive maintenance from her husband during the iddah period. This concept can be used as a basis for analyzing current conditions through an Islamic hermeneutic approach.